Effects of Viscosupplementation on Quality of Knee Joint Arthrokinematic Motion Analyzed by Vibroarthrography. (October 2021) - Bączkowicz, Dawid; Skiba, Grzegorz; Szmajda, Mirosław; Vařeka, Ivan; Falkowski, Krzysztof; Laudner, Kevin
Objective: To evaluate the influence of viscosupplementation on osteoarthritic knee arthrokinematics analyzed by VAG. It is considered that intra-articular hyaluronic acid injection may improve the function of synovial joints by recovery of friction-reducing properties of articular environment. Design: Thirty-five patients with knee osteoarthritis (grade II according to the Kellgren-Lawrence system) and 50 asymptomatic subjects were enrolled in the study. Patients were analyzed at 3 time points: 1 day before and 2 weeks and 4 weeks after single injection of 1.5% cross-linked hyaluronate. Control subjects were tested once. The vibroarthrographic signals were collected during knee flexion/extension motion using an accelerator and described by variation of mean square (VMS), mean range (R5), and power spectral density for frequency of 50 to 250 Hz (P1), and 250 to 450 Hz (P2). Results: Patients before viscosupplementation were characterized by about 2-fold higher values of vibroarthrographic parameters than controls. Two weeks after the procedure, the values of R5, P1, and P2 significantly decreased, in comparison to pre-injection. At 4 weeks post-injection, we noted a significant increase in R5, P1, and P2 values, when compared to 2 weeks post-injection. Finally, at 4 weeks post-injection, the level of VMS, R5, and P2 parameters did not differ from values obtained at pre-injection. Conclusions: We showed that viscosupplementation may be effective in providing arthrokinematics improvement, but with a relatively short period of duration. This phenomenon is observed as decreased vibroacoustic emission, which reflects a more smooth movement in the joint.